2017
DOI: 10.2147/ndt.s121517
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine monotherapy versus placebo in the treatment of children and adolescents with bipolar depression: a systematic review and meta-analysis

Abstract: BackgroundSome studies have indicated the efficacy of quetiapine in the treatment of bipolar depression in adult patients. However, its efficacy has been not shown in child and adolescent patients.ObjectiveThis systematic review purposefully determined the efficacy and acceptability of quetiapine in the treatment of children and adolescents with bipolar depression.Data sourcesA database search of EMBASE, PubMed, CINAHL, and Cochrane Controlled Trials Register was carried out in March 2016. All randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A meta-analysis revealed that quetiapine fumarate (50 mg and 150 mg) is indeed efficacious in acute treatment of adult patients with generalized anxiety disorder. 8 The positive effect of quetiapine on sleep disturbances observed in all our patients may explain its beneficial effect on 9 It is implausible that long-term SSRI treatment accounted for the positive antidepressant effect, because all patients developed BP-D despite continuous SSRI exposure. Moreover, limited therapeutic utility of SSRIs in BP-D and a detrimental effect on the course of BP were reported.…”
Section: Discussionmentioning
confidence: 80%
“…A meta-analysis revealed that quetiapine fumarate (50 mg and 150 mg) is indeed efficacious in acute treatment of adult patients with generalized anxiety disorder. 8 The positive effect of quetiapine on sleep disturbances observed in all our patients may explain its beneficial effect on 9 It is implausible that long-term SSRI treatment accounted for the positive antidepressant effect, because all patients developed BP-D despite continuous SSRI exposure. Moreover, limited therapeutic utility of SSRIs in BP-D and a detrimental effect on the course of BP were reported.…”
Section: Discussionmentioning
confidence: 80%
“…For antipsychotics, we included three NMAs 101‐103 , 11 MAs 104‐114 , 25 individual RCTs 115‐139 also included in those NMA/MAs, three additional RCTs 140‐142 , and two cohort studies 99,143 . There were 66,764 youth on antipsychotics, including 7,712 across 53 RCTs after eliminating duplicated RCTs in multiple NMA/MAs (6,725 in NMA/MAs, 987 in additional RCTs), and 59,052 in two cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…We ultimately included 14 NMAs and 90 MAs, reporting on 15 disorders or groups of disorders. For ADHD, we included three NMAs 5,20,21 and 21 MAs 22‐42 ; for autism, one NMA 43 and 21 MAs 12,44‐63 (including one focusing on comorbid anxiety disorders and autism) 12 ; for depressive disorders, two NMA 7,10 and seven MAs 64‐70 ; for obsessive‐compulsive disorder, one NMA 71 and six MAs 72‐77 ; for anxiety disorders, two NMAs 11,78 and five MAs 12,79‐82 (plus two MAs specific on social anxiety disorder 83,84 ); for enuresis, one NMA 85 and six MAs 86‐91 , for disruptive behavior/dissocial/conduct disorders, five MAs 92‐96 (plus one focusing on youth with comorbid ADHD) 25 ; for eating disorders, one NMA 97 and four MAs 98‐101 ; for schizophrenia spectrum disorders, three NMAs 8,102,103 and two MAs 104,105 ; for bipolar disorder, four MAs 106‐109 ; for tic disorder, two MAs 110,111 ; for Tourette's disorder, two MAs 112,113 ; for encopresis, two MAs 114,115 ; for developmental coordination disorder, one MA 116 ; and for PTSD, one MA 117 .…”
Section: Resultsmentioning
confidence: 99%